Sex and the treatment effect in the Chinese Medicine NeuroAiD Efficacy on Stroke recovery (CHIMES) trial. (November 2016) - Fabiaña, Natasha L.; Chen, Christopher L.H.; Venketasubramanian, Narayanaswamy; Lee, Chun Fan; Wong, K.S. Lawrence; De Silva, Deidre Anne
Highlights: Among women, there was a trend for a higher proportion with good functional outcome with NeuroAiD versus placebo ( p = 0.056). There was no treatment difference between NeuroAiD versus placebo in men ( p = 0.803). A trend for an interaction between sex and treatment was detected (odds ratio 1.13, p = 0.075). Abstract: In the randomized controlled trial of NeuroAiD versus placebo following ischemic stroke, there was a trend for sex influencing the treatment effect of NeuroAiD in improving functional outcome following ischemic stroke ( p = 0.075).